Perlawanan Syekh Syarip Prawira Sentana Dan Ki Sodewo Menentang Kolonialisme Belanda Di Kulon Progo 1839-1840 - Aditya Ayu Puspa Sari; Inast Mardatina Layyinah; Hidayatu Syarifah (Fakultas Adab dan Humaniora UIN Raden Fatah, 2022)
The presence of colonialism in Nusantara brought major changes in the social life of the people. The changes that occurred then led to an act of resistance as an effort to restore the social order that had been damaged. Socio-religious movements have become an important part of the history of local people's resistance to colonialism. Kulon Progo became one of the bases of religious social movements. One of the socio-religious movements that occurred in Kulon Progo was the resistance movement carried out by Sheikh Syarip Prawira Sentana and Ki Sodewo. The rebellion occurred in 1838-1840 M. This study discusses the socio-religious movement that was ignited by Sheikh Syarip Prawira Sentana and Ki Sodewo, covering the background of its occurrence in terms of socio-political, socio-economic, then a discussion of the brief profile of Sheikh Syarip Prawira Sentan and Sodewo and the chronology of the events of Syarip Prawira's resistance. Sentana and Ki Sodewo. This article uses the historical method and uses a sociological approach to be able to see the events of Syarif Prawira Sentana and Ki Sodeweo from a sociological perspective. Keywords: Kulon Progo Resistance, Religious Social Movement, Colonialism.